Systemic Therapy of Premenopausal Patients with Early Stage Hormone Receptor-Positive, HER2-Negative Breast Cancer - Controversies and Standards in Healthcare - Müller, Volkmar; Fasching, Peter; Nabieva, Naiba; Fehm, Tanja N.; Thill, Marc; Schmidt, Marcus; Kühn, Thorsten; Banys-Paluchowski, Maggie; Belleville, Erik; Juhasz-Böss, Ingolf; Untch, Michael; Kolberg, Hans Christian; et al. (Geburtshilfe und Frauenheilkunde, 2023)
In patients with existing ovarian function, there are some special aspects to adjuvant endocrine therapy in premenopausal patients with hormone receptor-positive, HER2-negative (HR pos./HER2 neg.) breast cancer. Treatment options include tamoxifen with or without a GnRH analog, and aromatase inhibitors with a GnRH analog. Furthermore, ovarian function is affected by previous chemotherapy. Both aromatase inhibitors (+GnRH analogs) and GnRH analogs in combination with tamoxifen are supposed to be indicated for patients at increased risk of recurrence. However, national and international guidelines and therapy recommendations do not provide a clear definition of intermediate or high risk; as a result, therapy decisions are often made for each patient on an individual basis. This is also reflected in the considerable variability at national and international levels, e.g., with regard to the use of aromatase inhibitors + GnRH analogs. This review summarizes the data on completed studies (e.g., SOFT, TEXT, EBCTCG meta-analyses) and the current multigene testing studies (TailorX, RxPonder, ADAPT), discusses the rationale for current studies (e.g., CLEAR-B), and looks ahead to future questions.
CRIS-Team Scopus Importer:2023-06-23
Keywords: aromatase inhibitor; breast cancer; GnRH; premenopausal therapy; tamoxifen